2015
DOI: 10.1016/j.jcrs.2014.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Refractive outcomes of Descemet membrane endothelial keratoplasty triple procedures (combined with cataract surgery)

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 23 publications
5
89
0
Order By: Relevance
“…Owing to the excellent visual outcome and refractive stability achieved after DMEK [5, 12], (toric) IOL power calculations in patients after phakic DMEK or within the setting of the new triple procedure are becoming a topic of much interest in clinical practice [18, 19]. As previously described, the change in corneal refractive power after DMEK is based mainly on changes in the posterior corneal curvature, whereas the anterior corneal curvature does not alter significantly [5, 11].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the excellent visual outcome and refractive stability achieved after DMEK [5, 12], (toric) IOL power calculations in patients after phakic DMEK or within the setting of the new triple procedure are becoming a topic of much interest in clinical practice [18, 19]. As previously described, the change in corneal refractive power after DMEK is based mainly on changes in the posterior corneal curvature, whereas the anterior corneal curvature does not alter significantly [5, 11].…”
Section: Discussionmentioning
confidence: 99%
“…The changed corneal power and the hyperopic shift after triple DMEK have been described in various studies in the literature [ 7 9 ]. Both Schoenberg et al and our group showed that the anterior curvature did not significantly change after DMEK [ 8 , 9 ]. Morphological changes in posterior curvature of the cornea are to be expected after DMEK, because DMEK surgery acts mainly on the backside of the cornea.…”
Section: Discussionmentioning
confidence: 91%
“…Given the promise of near complete visual recovery and refractive stability over time with this procedure [ 7 , 22 ], increasing interest is being focused on IOL power calculations for cataract surgery prior to, in the same setting or after DMEK. In clinical practice, hyperopic outcomes tend to occur after endothelial keratoplasty and in the past many surgeons have aimed to achieve a more myopic postoperative outcome and choose a refractive target of −0.75 to −1.00 D to reduce the chance of unintended hyperopic surprises [ 8 , 11 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty percent of patients will get a slightly myopic shift, and 60% of patients will get a hyperopic shift. The induced refractive shifts range from −0.5 to +2.0 D.[23]Once you master the DMEK with simple corneal edema, you can perform more complex cases, such as cases with a failed PK, or advanced cases with pseudophakic bullous keratoplastyIn cases with very edematous cornea, remove the thick epithelium from the swollen cornea to improve your view. Perform DMEK in more challenging cases with a very swollen cornea when you are comfortable with the procedureAvoid eyes which had previous vitrectomy, filtration surgeries, AC-IOL implantation, etc.…”
Section: Suggestions For the Beginnermentioning
confidence: 99%